2018
DOI: 10.1186/s12906-018-2115-y
|View full text |Cite
|
Sign up to set email alerts
|

Citral induced apoptosis in MDA-MB-231 spheroid cells

Abstract: BackgroundBreast cancer remains a leading cause of death in women worldwide. Although breast cancer therapies have greatly advanced in recent years, many patients still develop tumour recurrence and metastasis, and eventually succumb to the disease due to chemoresistance. Citral has been reported to show cytotoxic effect on various cancer cell lines. However, the potential of citral to specifically target the drug resistant breast cancer cells has not yet been tested, which was the focus of our current study.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 27 publications
3
30
0
Order By: Relevance
“…Regarding its antineoplastic potential, the EOCc showed an anti-cancer effect on cervical cancer cell lines and breast cancer cell line, MCF-7 [ 21 , 22 , 23 ] Likewise, citral induced apoptosis in several hematopoietic cancer cell lines, accompanied by DNA fragmentation and induction of the catalytic activity of caspase-3 [ 24 ], and in ovarian cancer cell lines [ 25 , 26 ]. Additionally, carvacrol, a monoterpenes-phenol is found in the essential oil of many aromatic plants of the Lamiaceae family, including thyme and oregano, showed its anti-cancer potential on the human metastatic breast cancer cell line [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding its antineoplastic potential, the EOCc showed an anti-cancer effect on cervical cancer cell lines and breast cancer cell line, MCF-7 [ 21 , 22 , 23 ] Likewise, citral induced apoptosis in several hematopoietic cancer cell lines, accompanied by DNA fragmentation and induction of the catalytic activity of caspase-3 [ 24 ], and in ovarian cancer cell lines [ 25 , 26 ]. Additionally, carvacrol, a monoterpenes-phenol is found in the essential oil of many aromatic plants of the Lamiaceae family, including thyme and oregano, showed its anti-cancer potential on the human metastatic breast cancer cell line [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…e therapeutic use of this oil was due to the presence of monoterpenes and myrcene. Few studies demonstrated the anticancer properties of citral in various cancer cell lines including breast (MDI-MB-231), small-cell lung cancer, colorectal cancer (HCT116 and HT29), and cervical cancer (HeLa and ME-180) [12,[29][30][31]. Although various studies in a preliminary level of citral have been studied against various cancer cell lines, the effect of cis-and trans-citral on aggressive prostate cancer (PC3) has not been elucidated so far.…”
Section: Discussionmentioning
confidence: 99%
“…Obtained IC 50 values were dependent on structure of monoterpene molecule as well as on cancer cell line used. For linearly-shaped citral, IC 50 values ranged from 10–15 µM in melanoma cell lines [ 25 ] to 60–80 µM in breast [ 26 ] and small cell lung cancer [ 27 ]. On the other hand, cyclic monoterpenes were usually characterized by IC 50 values close to several hundred µM (e.g., β-elemene [ 28 ], safranal [ 29 ], carvacrol, and thymol [ 30 ]); however, one study reported IC 50 values below 1 µM [ 31 ].…”
Section: Discussionmentioning
confidence: 99%